PROFIL PEMECAHAN MASALAH KELILING DAN LUAS LINGKARAN SISWA KELAS IX A SMP NEGERI 1 TINOMBO DITINJAUDARI KEMAMPUAN AWAL: Problem Solving of Circumference and Area of Circle For IX A Grade Students of SMP Negeri 1 Tinombo Based On Initial Ability - Zidan H.L, Moh.; Murdiana, I Nyoman; Idris, Mustamin (Universitas Tadulako, 2024)
This research aims to describe the problem solving profile of the circumference and circle area of ​​students in Class IX A of SMP Negeri 1 Tinombo in terms of initial abilities. This type of research is qualitative research with a qualitative descriptive approach based on Polya's problem solving steps. The results of the research show that the problem solving profile of the circumference and area of ​​a circle is for students who have: (1) high initial abilities and medium initial abilities: a) understanding the problem, at this stage students can identify things that are known using statement sentences and things that are asked using question sentences. b) planning problem solving, at this stage students plan solving the problem of the circumference and area of ​​a circle well. c) carry out a problem solving plan, at this stage students can apply problem solving strategies appropriately based on mastery of the circle concept and accuracy in finding solutions to the problems given and students carry out as planned. d) rechecking the answers, at this stage students check the results of their work step by step and recalculate the results obtained. (2) low initial ability: a) understanding the problem, at this stage students can mention things they know and ask questions but cannot understand all the information from the problem given. b) planning problem solving, at this stage students are not able to determine ways or strategies to solve problems. c) carry out a problem solving plan, at this stage students cannot solve the problem given because they have the wrong final answer because they do not use information in the form of things they know correctly so that students have difficulty finding a solution to the problem. d) rechecking answers, at this stage students cannot recheck answers.